Duration Dependence in the Exit Rate out of Unemployment in Belgium: Is It True or Spurious? - Bart Leo Wim Cockx; Muriel Dejemeppe (Institute for the Study of Labor (IZA), 2002)
On the basis of aggregate data for the early nineties, we analyse the determinants of unemployment duration for laid-off male workers in Wallonia (Belgium). Our results demonstrate that if ranking in recruitment occurs, the standard Mixed Proportional Hazard specification can be too restrictive, leading to an overstatement of the extent of true negative duration dependence. We conclude that negative duration dependence is largely spurious. We also decompose the time variation of the hazard in (unobserved) compositional and direct cyclical and seasonal effects. We find counter-cyclical variation in the quality of young workers, but none for the prime aged.
Keywords: J64; C41; 330; unemployment duration; ranking; heterogeneity; business cycle; Arbeitslosigkeit; Dauer; Berufliche Integration; Konjunktur; Schätzung; Belgien